The Impact of Marketing Expenditure on Firm Performance - Haryanto, Totok; Retnaningrum, Maharani (Universitas Muhammadiyah Yogyakarta, 2020)
This study aimed to examine whether marketing expenditure affected firm performance. Previous research has mentioned that there was an influence between marketing expenditure to profitability and firm value. However, some stakeholders and practitioners perceived that the budget for marketing expenditure has already overspent, which means it was assumed that marketing expenditure is very high cost and difficult to measure. In this research, the contribution of marketing expenditure to firm performance of the big four of the telecommunication companies in Indonesia (PT. Telkom, Tbk (including PT. Telkomsel), PT. Indosat Ooredoo, Tbk, PT. XL Axiata, Tbk, and PT. Smartfren Telecom, Tbk) would be analyzed. Firm performance was proxied as the profit margin on sales (PM on Sales), return on assets (ROA), return on investment (ROI), and return on equity (ROE). The methodology of the research used the quantitative model, and the analysis applied the simple regression. The results showed that the marketing expenditure had a significant effect on PM on Sales, ROI, and ROE, partially. On the contrary, the marketing expenditure had no impact on the return on assets (ROA).